“The Recognition of Rights and Capabilities on Fichte’s Theory of Natural Right” - Arrese, Héctor (2014)
In this paper I try to reconstruct the arguments developed by Fichte in his work Foundations of Natural Right (1796/1797), in order to support the necessity of a recognition of capabilites and rights by the other, so that the I can constitute itself as a self-consciousness. I also take into account the criticisms the Fichtean theory has received by many contemporary interpreters, testing its consistency in the light of these arguments.